2017
DOI: 10.2147/ott.s135312
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differential co-expression patterns reveal transcriptional dysregulation mechanism and identify novel prognostic lncRNAs in esophageal squamous cell carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignancies worldwide and occurs at a relatively high frequency in People’s Republic of China. However, the molecular mechanism underlying ESCC is still unclear. In this study, the mRNA and long non-coding RNA (lncRNA) expression profiles of ESCC were downloaded from the Gene Expression Omnibus database, and then differential co-expression analysis was used to reveal the altered co-expression relationship of gene pairs in ESCC tumors. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 64 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…ADAMTS9-AS1 is an antisense lncRNA, and growing evidence has implicated that a large amount of antisense lncRNAs play crucial roles in the cancer [ 35 , 36 ]. Li et al [ 37 ] reported that ADAMTS9-AS1 could predict the survival status of patients with esophageal squamous cell carcinoma. Another study has also indicated a prognostic role of ADAMTS9-AS1 in patients with colon adenocarcinoma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS9-AS1 is an antisense lncRNA, and growing evidence has implicated that a large amount of antisense lncRNAs play crucial roles in the cancer [ 35 , 36 ]. Li et al [ 37 ] reported that ADAMTS9-AS1 could predict the survival status of patients with esophageal squamous cell carcinoma. Another study has also indicated a prognostic role of ADAMTS9-AS1 in patients with colon adenocarcinoma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of four lncRNAs biomarkers, AP000696.1 is essential in the development of ectoderm and epithelial cells, and may sever as prognostic biomarker (Li et al, 2017). It has been reported that LINC00900 is significantly up-regulated by all-trans-retinoic acid and down-regulated by vitamin D (Riege et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (36) revealed that antisense lncRNA ADAMTS9-AS1 was associated with the nearby coding gene ADAMTS9, which was involved in ovarian cancer progression. Li et al (37) identified that the lncRNA ADAMTS9-AS1 served as a novel prognostic biomarker for clinical application in esophageal squamous cell carcinoma. Crippa et al (38) hypothesized that LINC00536 disruption may have contributed to the onset of the clinical trichorhinophalangeal syndrome-like phenotype.…”
Section: Discussionmentioning
confidence: 99%